2016
DOI: 10.1007/s12603-015-0707-5
|View full text |Cite
|
Sign up to set email alerts
|

Is meeting the recommended dietary allowance (RDA) for protein related to body composition among older adults?: Results from the Cardiovascular Health of Seniors and Built Environment Study

Abstract: Objective Studies suggest protein intake may be associated with lower body weight, but protein has also been associated with preservation of lean body mass. Understanding the role of protein in maintaining health for older adults is important for disease prevention among this population. Design Cross-sectional study of the relationship of dietary protein on body composition. Setting New York City community centers Participants 1,011 Black, White, and Latino urban men and women 60-99 years of age Measur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
29
0
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(31 citation statements)
references
References 28 publications
1
29
0
1
Order By: Relevance
“…Accordingly, the CC group showed a small increase in relative protein consumption from baseline (0.83 g·kg −1 ·day −1 ) to 12 W (0.98 g·kg −1 ·day −1 ). These changes remained within the relative protein consumption guidelines for physically active individuals (Beasley et al 2016;Thomas et al 2016). The CC group also engaged in resistance training, which is also associated with the maintenance of lean body mass (Strandberg et al 2015).…”
Section: Discussionmentioning
confidence: 58%
“…Accordingly, the CC group showed a small increase in relative protein consumption from baseline (0.83 g·kg −1 ·day −1 ) to 12 W (0.98 g·kg −1 ·day −1 ). These changes remained within the relative protein consumption guidelines for physically active individuals (Beasley et al 2016;Thomas et al 2016). The CC group also engaged in resistance training, which is also associated with the maintenance of lean body mass (Strandberg et al 2015).…”
Section: Discussionmentioning
confidence: 58%
“…The observation of an inverse association between protein (g/kg) and calf circumference went against expectations, since calf circumference is a parameter to estimate muscle mass in clinical practice. Beasley et al [24], in a crosssectional study with 1,011 community-dwelling elderly, also identified an unexpected association between protein (g/kg) and anthropometric measure. The authors have noted an inverse association with skeletal mass (kg), regardless of sex.…”
Section: Discussionmentioning
confidence: 88%
“…Other studies also reported conflicting results with protein intake and other disability-associated variables (e.g., low skeletal muscle mass). Gregorio et al [25] and Beasley et al [51] reported that older adults consuming >0.8 g protein/kg/d showed lower skeletal muscle mass than those consuming protein below this threshold, and Isanejad et al [24] reported that sarcopenic women ate more relative protein (g/kg/d) than their non-sarcopenic counterparts. It is possible that higher relative protein intake is observed in sarcopenic or disabled people because of their lower body weight [52].…”
Section: Discussionmentioning
confidence: 99%
“…The association between protein intake and lower physical disability risk may also be mediated by its role in decreasing body fat [26,51,56]. As we get older, there is an increase in body fat and fat infiltration into the muscle [57], which leads to decreased muscle quality, strength, and functionality [6,24,58,59].…”
Section: Discussionmentioning
confidence: 99%